2014
DOI: 10.4236/ajps.2014.515245
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oil and Nitrogen Metabolism of Menthol Mint under Different Phosphorus Levels

Abstract: The purpose of this work was to evaluate the effects of different phosphorus levels (0.05, 0.5, 1 and 2 mM) under nitrogen metabolism and the essential oil profile of menthol mint (Mentha arvensis L.). The relationship between the leaf maturity and the essential oil profile was also explored. The experiment was conducted in a hydroponic system located in a grow chamber during 41 days and after the harvest, nitrate reductase activity, and the NO− -N, amino-N, and soluble sugars levels of each plant part were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…However, between the young and adult leaves, it was observed increased concentrations of menthol (9%) and menthyl acetate (330%) in mature leaves and a decrease of menthone (71%) in young leaves ( Table 1). Similar results were showed by others authors [26] [28] [30].…”
Section: Description Of the Experiments And Statisticalsupporting
confidence: 93%
See 1 more Smart Citation
“…However, between the young and adult leaves, it was observed increased concentrations of menthol (9%) and menthyl acetate (330%) in mature leaves and a decrease of menthone (71%) in young leaves ( Table 1). Similar results were showed by others authors [26] [28] [30].…”
Section: Description Of the Experiments And Statisticalsupporting
confidence: 93%
“…The results showed that the young leaves are associated with higher content of limonene and ketone monoterpenes, intermediates in the biosynthesis of menthol, on the other hand, the adult leaves presented higher contents of alcohols and esters monoterpene (Note in Figure 2 the numbers marked with asterisk) [30]. Table 2 shows that essential oil affected partially the development of the fungus F. oxysporum, R. solani and S. rolsii.…”
Section: Essential Oil Content and Chemical Analysismentioning
confidence: 93%